A SCAFFOLDING STRATEGY IN THE PROCESS OF WRITING FOR YOUNG LEARNERS - Ningrum, Ary Setya Budhi (Pusat Pengembangan Bahasa IAIN Tulungagung, 2011)
The main issue underlying the teaching of English in primary school is as a part of the national development that is directed towards the improvement of the quality of human resources. One aspect of this goal is the improvement of the mastery of foreign languages, particularly the English language (Huda, 1999). As a foreign language, English belongs to the difficult subject to teach for young learners, especially for writing skill. This article tries to offer a scaffolding strategy in the process of writing as an alternative way of teaching method in teaching writing to young learners. This method provides step-by-step guidance in writing that is suitable to young learners? characteristics.